Gain Enhancement of Circularly Polarized Aperture-Coupled Microstrip Patch Antenna Using Partially Reflective Surface - Supreeyatitikul, Nathapat; Boonpoonga, Akkarat; Phongcharoenpanich, Chuwong (My University, 2022)
This paper proposes a compact and high-gain circularly polarized H-shaped aperture-coupled cornertruncated square microstrip patch antenna with partially reflective surface for C-band applications. The H-shaped aperture-coupled corner-truncated square patch antenna performed a right-handed circularly polarized radiation. The PRS was utilized to enhance bandwidth and gain, which placed above (air gap) the CP H-shaped aperture-coupled microstrip patch antenna. The PRS contained 8×8 arranged-periodically rhombus-shaped unit cells on the FR-4 single-substrate. Simulations of the proposed CP antenna with PRS at 4.5 GHz (center frequency) achieved impedance bandwidth, axial ratio bandwidth, and maximum gain of 37.7% (4-5.7 GHz), 13.3% (4.3-4.9 GHz), and 12 dBi at 4.7 GHz. The overall dimension antenna was 100 mm x 100 mm x 43.2 mm. Essentially, a high gain of the proposed antenna is suitable for C-band frequency.
Keywords: Aperture-coupled; C-band; CP radiation; partially reflective surface; square microstrip patch antenna